HUBUNGAN ANTARA GAYA KEPEMIMPINAN WANITA DAN KINERJA PEKERJA PADA LINGKUNGAN ANEKA ETNIS DAN ANEKA BUDAYA - Wijiastuti (UTP Surakarta), Sri (Manajemen Bisnis Syariah, 2011)
The research have two aim, first for knowing and proving are the independences variable such as assumption, trust, interpersonal relationship and social structure have related of simultaneous or partials which productivity .for work Second for the identification are the independent variables haves more dominant effect to productivity for work on multi culture. According to the method, type of this research is survey research. Collect data method using questionnaire. Samples where taken by use random sampling method which 63 woman worker responded on building contractor and other relation contractor building organizations on Surakarta. The result of the research conclude that independent variables have strong correlation to dependent variable with R= 0.745, while coefficient determination (R2) is 0.630. It means that independent have contribution about 63% influencing dependent variable, while 37% influenced by other variables that not include to the models. That independent variable consisting assumption, trust, and social structure have significant influence toward dependent variable (productivity), while interpersonal relationship have not significant influence to dependent variable. Which show the value of t =-3.082 and probability 0.452 greater than 0.05. Between the independent variable that assumption have most important dominant variable gives effect to the productivity also show beta coefficient of 0.803. Building contractor and other relation contractor building organizations on Surakarta be desirable that attention to interpersonal relationship have not effect to productivity with notice of financial factors for majoring of work of guarantee, physical, socials and employee psychology.   Keywords: assumption; trust; interpersonal relationship; social structure.